Fabrication and Evaluation of Gemcitabine-loaded Alginate Microspheres: A Potential Approach for Treatment of Various Carcinomas - Hossain, Maruf; Chatterjee, Shayeri; Paria, Hiranmoy; Ganguly, Soumya (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/background: Microspheres are spherical particles, having a core, having a particle size of 1μm to 1000μm. They are advantageous as compared to conventional dosage forms of drugs, in parameters like sustainability and control of drug release, drug protection, biodegradability, targeting ability and many more. Gemcitabine is a prodrug and is used in various carcinomas. Sodium Alginate and Ethyl Cellulose are used as polymers. The fabrication aims to sustain the drug release which can treat pancreatic, breast, ovarian and lung cancer. Materials and Methods: Microspheres have been made by Ionotropic Gelation method, Sodium alginate, Ethyl cellulose and Calcium chloride. Weighed quantity of drug and polymer were added to sodium alginate solution, which was then added drop wise to Calcium chloride solution under continuous stirring to procure spherical rigid microspheres. These were then subjected to various physicochemical characterizations and surface analysis. Results and Conclusion: Results have shown that by increasing the polymer concentration, entrapment efficiency and drug loading have also increased. Particle size, SEM and micromeritic evaluation have exhibited satisfactory results. The drug release studies depict that most of the batches have showed less than 10% release acid media so it protects the drug from the upper part of GI Tract. These attributes prove that microsphere technology, being a crucial novel drug delivery system can be very effective in reducing dose frequency, dose dumping and better patient compliance.
Keywords: Gelation; Targeting; Sustainability; Microspheres; Entrapment Efficiency